PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR DANA MANDIRI KABUPATEN BOGOR - Mustika, Sinta; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of leadership and motivation on employee performance at PT BPR Dana Mandiri, Bogor Regency. The method used is quantitative. The population in this study was 83 respondents. The results of the analysis show that motivation has a significant effect on employee performance with a significant value of 0.03 < 0.05, and the t count is 3.064 > 1.990 t table. The physical work environment has a significant effect on employee performance with a significant value of 0.000 < 0.05, and a calculated t value of 13.653 > 1.990 t table. Motivation and Physical Work Environment have a significant effect on Employee Performance with the regression equation Y= 2.081+ 0.161X₁ + 0.791X₂. The coefficient of determination value is 8.81% while the remaining 0.91% is influenced by other variables outside this regression equation or variables that are not examined. Hypothesis testing obtained a calculated F value > F table or (296.167 > 3.11).